EXPLORING NEW PARADIGMS OF RESEARCH PRACTICE IN DEVELOPING GLOBAL MARKET (CAHIERS MAGELLANES-NS, 2024)
The areas of research methodologies are continually developing, driven by the quest for more profound comprehension and more successful critical thinking. This theory examines the concept of exploring new paradigms of research practice, featuring the meaning of embracing advancement in the journey for information revelation. It looks at the reasoning behind the requirement for novel methodologies, focusing on the restrictions of conventional approaches and the open doors introduced by investigating new roads. By embracing new paradigms, researchers can be liberated from the limitations of regular reasoning and procedures, opening ways to new points of view and insights. This paper explores various examples of innovative research paradigms, ranging from interdisciplinary collaborations and data-driven approaches to participatory action research and qualitative synthesis methods. It discusses how these paradigms offer unique opportunities to address complex research questions and tackle emerging challenges in diverse fields.Besides, this paper talks about the likely advantages and difficulties related to taking on new research paradigms, including considerations connected with interdisciplinary collaboration, strategic exactness, and moral ramifications. It underscores the significance of encouraging a culture of trial and error and advancing within the research community to work with the investigation and reception of inventive methodologies.